SERTULUM DIPTEROCARPACEARUM MALAYENSIUM-”V* - D. F. VAN SLOOTEN (Research Center for Biology, 1952)
Some 70 years ago Thiselton Dyer showed Dipterocarpaceae from New Guinea to the Linnean Society of London. This event is referred to in the